Uptake and release characteristics of serotonin hydrochloride by natural Cuban zeolite containing clinoptilolite and mordenite - Jan-Paul Grass (Nature Portfolio, 2021)
Abstract Serotonin (5-HT) plays an important role in human physiology. An excess of this native regulator within the human gut can be partially controlled by orally consuming zeolite. Therefore, this study focuses on the kinetics of the uptake and release of serotonin hydrochloride (5-HT-hc) by natural Cuban zeolite containing clinoptilolite and mordenite at different pH levels using UV–Vis spectroscopy. 5-HT-hc is stable under the following investigated experimental conditions: incubation temperature of 36 °C; and at a pH of 5, 7, and 9. Independent of the zeolite framework, the 5-HT-hc is adsorbed without changing its molecular structure. The uptake and release of 5-HT-hc were not correlated to the textural properties of these aluminosilicates. The investigated zeolites adsorbed 5-HT-hc at about 14 mg per gram zeolite with no large differences observed between different samples. Release studies of 5-HT-hc-loaded zeolite revealed that the 5-HT-hc is strongly bound to the zeolite, and independent of the pH value and zeolite framework only up to 12.7% was released into the water.